Analisis implementasi disiplin kerja dalam upaya meningkatkan kinerja karyawan divisi nds pada pt. Adira finance cabang sawangan - Maya Ameliani; Muhamad Guruh (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study is entitled “Analysis of the Implementation of Work Discipline in Efforts to Improve Employee Performance in the NDS Division at PT. Adira Finance Sawangan Branch.” The background of this research is based on the importance of work discipline as a key factor influencing employee performance in achieving organizational goals. Good work discipline encourages compliance with regulations, punctuality, and adherence to standard procedures, which in turn improve productivity and work effectiveness. The purpose of this research is to analyze the implementation of work discipline and its contribution to improving employee performance in the NDS Division of PT. Adira Finance Sawangan Branch. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews with four key informants (Branch Manager, NDS Division Head, and two Relationship Officers), observations, and documentation. Data analysis was carried out using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. The results show that the implementation of work discipline in the NDS Division has been applied through punctuality, compliance with standard operating procedures (SOP), and timely submission of work reports. Work discipline is proven to play an important role in supporting employee performance improvement, both individually and as a team. Employees with high discipline demonstrate higher productivity, task accuracy, and consistency in achieving company targets.